25G lens resection combined with anterior vitrectomy in the treatment of congenital cataract - Fu-Rong Liao (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM: To observe the clinical efficacy of 25G lens resection combined with anterior vitrectomy in the treatment of congenital cataract.METHODS: This retrospective case series study included 55 eyes of 38 children with congenital cataract, age from 3mo to 5 years old, who were recruited between May 2013 and August 2017. The children were divided into two groups according to the different surgical methods. Group A(25 eyes of 17 children)received a 25G sutureless lensectomy combined with capsulotomy and anterior vitrectomy, and group B(30 eyes of 21 children)received a cataract phacoemulsification combined with capsulotomy and anterior vitrectomy. The mean follow-up time was 43.4(range: 36-74)mo. The postoperative best corrected visual acuity(BCVA), axial length, and complications were compared. RESULTS: The age, sex distribution, duration, preoperative BCVA, and preoperative axial lengths were not significantly different between the two groups(P>0.05). The BCVA improved significantly at postoperative compared with BCVA at baseline in both gorups(Group A: P<0.001; Group B: P<0.001). The BCVA was better in Group A than Group B at 6mo postoperatively(P=0.043). No statistically significant difference was found in BCVA between the two groups at 12, 24 and 36mo after initial treatment(P=0.727, P=0.286, P=0.889). No statistically significant difference was found in axial lengths between 6mo of postoperation and preoperation in both groups(Group A: P=0.206, Group B: P=0.082). The mean postoperative axial lengths at 12, 24 and 36mo were longer than that at baseline in both group(Group A: P=0.023, P=0.015, P<0.01, Group B: P=0.018, P<0.01, P<0.01). There were no significantly different in mean axial length after operation between the two groups(6mo: P=0.195, 12mo: P=0.313, 24mo: P=0.485, 36mo: P=0.089). The rate of postoperative complications was lower in Group A than Group B(P=0.042).CONCLUSION: 25G sutureless lensectomy combined with capsulotomy and anterior vitrectomy is an effective and safe treatment method for congenital cataract, the visual acuity after treatment was improved significantly.